2007
DOI: 10.1002/aic.11381
|View full text |Cite
|
Sign up to set email alerts
|

Free surface flow in the mixing zone of an annular centrifugal contactor

Abstract: in Wiley InterScience (www.interscience.wiley.com).The annular centrifugal contactor has been developed as the central piece of equipment for advanced liquid-liquid extraction processes for use in recycling spent nuclear fuel. While a sufficient base of experience exists to support successful operation of current contactor technology, a more complete understanding of the fluid flow within the contactor would enable further advancements in design and operation of future units. In particular, an important charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 27 publications
7
51
0
1
Order By: Relevance
“…The LDV setup was described previously in , 12 and consisted of a two-component measuring system. Because of the contactor's annular geometry, only backscatter measurements were possible, and, therefore, a transceiver was used rather than an off-axis or forward scatter receiver.…”
Section: Laser Doppler Velocimetry (Ldv)mentioning
confidence: 99%
“…The LDV setup was described previously in , 12 and consisted of a two-component measuring system. Because of the contactor's annular geometry, only backscatter measurements were possible, and, therefore, a transceiver was used rather than an off-axis or forward scatter receiver.…”
Section: Laser Doppler Velocimetry (Ldv)mentioning
confidence: 99%
“…(13) Wardle et al [141] have presented a comparison of experimental measurements and computational modeling of the free surface flow in the mixing zone of an annular centrifugal contactor. It was found that CFD modeling using the LES turbulence simulation method even for a relatively coarse computational grid was able to qualitatively and quantitatively predict the actual dynamics of the flow in the contactor mixing zone.…”
Section: Discussionmentioning
confidence: 99%
“…Wardle and coworkers were the first to attempt to apply free-surface capturing CFD methods to simulate gas-liquid free surface flow in the centrifugal contactor mixing zone at relevant conditions [27,141]. Using volume of fluid (VOF) methods [142] and the commercial code Fluent, the freesurface flow in a lab-scale centrifugal contactor having a 50.8 mm rotor was explored [141].…”
Section: International Journal Of Chemical Engineeringmentioning
confidence: 99%
See 2 more Smart Citations